The Substitute Notary's Responsibility for the Deed He Made - PUTRA, Gede Bagus Andika; DHARSANA, I Made Pria; WESNA, Putu Ayu Sriasih (Journal of Political And Legal Sovereignty, 2024)
Purpose: A Substitute Notary is temporarily appointed as a Notary to replace a Notary who is on leave or sick. In Article 65 of the UUJNP, there is no explanation regarding the limits of the Substitute Notary's liability after his/her term ends. It is illogical because the limits of the Substitute Notary's authority end when the limits stated in his/her decision letter have expired, and he/she must still be responsible until his/her last breath.Methodology:The author uses a normative legal research method, legislative approach, legal concept analysis, case approach and comparative approach. The author's legal sources use primary and secondary law and tertiary legal materials. The legal collection technique uses document study techniques and recording.Findings: The responsibilities of a substitute notary can be divided into 4, namely: (1) Civil Liability of a Substitute Notary, (2) Criminal Liability of a Substitute Notary, and (3) Administrative Liability of a Substitute Notary. Legal protection for a substitute notary can be divided into 2: preventive legal protection and repressive protection.Implication:The responsibility of the Substitute Notary is only in the formal form of the authentic deed as stipulated in the law, so the Notary is not responsible for the contents of the deed. When carrying out their duties, a substitute notary will receive legal protection, including preventive legal protection to prevent disputes from occurring and repressive protection to resolve disputes that have already occurred. It is outlined in Article 66 of the UUJNP as a form of settlement effort if the notary is questioned.